Optimization of Sybr Green Quantitative Real Time Polymerase Chain Reaction (qPCR) using Excreted-Secreted Antigens (ESAs) Genetik Marker for Detection Toxoplasma gondii - Ekawasti, Fitrine; Winarsongko, Agus; Nepho, Farlin; Purwanto, Eko Setyo; Subekti, Didik Tulus; nuradji, harimurti; Dharmayanti, NLP Indi; Ahmad, Riza Zainuddin; Sa’diah, Siti; Cahyaningsih, Umi; Nurcahyo, Raden Wisnu (Jurnal Sain Veteriner, 2024)
AbstractToxoplasma gondii is an obligate intracellular parasite, causing toxoplasmosis in almost all warm-blooded animals and humans worldwide. Toxoplasmosis is a zoonotic disease of serious public health concern. Host cell invasion by T. gondii tachyzoites has process involving the sequential secretion of Excreted-Secreted Antigens (ESAs). T. gondi ESAs could be a valuable candidate for the diagnosis of toxoplasmosis. Techniques to more accurately detection of T. gondii recently developed biotechnological methods that are currently being used, conventional and real time Polymerase Chain Reaction (RT-PCR). RT-PCR is more widely used because it is more sensitive and specific. The aims of this study were to optimize the Sybr Green RT-PCR in different region gene based on Excreted-Secreted Antigens (ESAs), tachyzoite surface antigen and bradhyzoite antige, then adapt the conventional PCR program to real-time PCR for detection Toxoplasma gondii. Optimization is necessary to get optimal condition of PCR to get the best results. T. gondii RH strains derived from liquid nitrogen and DNA extracted by DNAzol. The genetic marker used GRA1#1, GRA1#2, GRA7#1, GRA7#2, ROP1, MIC3, SAG1 and BAG1. The results of the optimization of multiple primer genes can adapt and be used optimal in RT-PCR by using the same cycle program simultaneously in one run. Overall, RT-PCR for the detection of T. gondii DNA demonstrated excellent agreement with conventional PCR. RT-PCR with melting curve analysis is rapid and simple that facilitates high throughput analysis to detect T. gondii. The optimal conditions obtained from the optimization results can facilitate further research to detect T. gondii.Keywords: Biotechnology molecular, Detection, excretory-secretory antigen, toxoplasmosis